2018
DOI: 10.1093/ntr/nty065
|View full text |Cite
|
Sign up to set email alerts
|

Cardiovascular Effects of Hookah Smoking: Potential Implications for Cardiovascular Risk

Abstract: This review provides an overview on the potential impact of hookah smoking on cardiovascular health. Readers will gain an insight into evidence on its toxicological constituents, human health effects, and pathophysiological mechanisms by which hookah smoking might cause cardiovascular disease. The review also highlights current research gaps regarding the cardiovascular consequences of hookah smoking, specifically the long-term consequences in the U.S. and Europe among flavored hookah tobacco users.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
40
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 58 publications
(43 citation statements)
references
References 81 publications
2
40
0
1
Order By: Relevance
“…The majority of the physicians believed that patient incompliance, limited training and knowledge on smoking cessation, lack of available cessation programs, patients' disinterest in quitting and lack of time during patient consultation are very important barriers that interfere with promoting waterpipe smoking cessation. Our findings are consistent with earlier studies conducted in Gulf countries and Europe that have examined factors influencing PCPs' engagement in smoking cessation [9,17,20,21], which have revealed time constraint [21,[33][34][35], lack of training [21,28,[33][34][35], and patients' disinterest in quitting [28] to be the most common perceived barriers among healthcare professionals. Interestingly, 50% of the physicians did not believe that their own smoking status is an important barrier that affects their smoking cessation practices which is in accordance with studies performed in Palestine, Kuwait, and Bahrain where respondents were in the lowest agreement with the statement.…”
Section: Physicians' Perceived Barriers To Providing Wts Cessation Insupporting
confidence: 92%
See 1 more Smart Citation
“…The majority of the physicians believed that patient incompliance, limited training and knowledge on smoking cessation, lack of available cessation programs, patients' disinterest in quitting and lack of time during patient consultation are very important barriers that interfere with promoting waterpipe smoking cessation. Our findings are consistent with earlier studies conducted in Gulf countries and Europe that have examined factors influencing PCPs' engagement in smoking cessation [9,17,20,21], which have revealed time constraint [21,[33][34][35], lack of training [21,28,[33][34][35], and patients' disinterest in quitting [28] to be the most common perceived barriers among healthcare professionals. Interestingly, 50% of the physicians did not believe that their own smoking status is an important barrier that affects their smoking cessation practices which is in accordance with studies performed in Palestine, Kuwait, and Bahrain where respondents were in the lowest agreement with the statement.…”
Section: Physicians' Perceived Barriers To Providing Wts Cessation Insupporting
confidence: 92%
“…However, there exists compelling evidence about the harms of waterpipe smoking and detrimental effect on long-term health outcomes [7,8]. More specifically, several systematic reviews and metaanalyses have demonstrated the association between WTS and increased risk of lung cancer, cardiovascular diseases, abnormal pulmonary function, low birth weight, and periodontal diseases [4,[9][10][11]. Despite the evidence, the incorrect public perception of reduced harm is possibly driven by the introduction of flavored waterpipe tobacco (also known as Maassel), the advancement of global communication particularly the internet, and the lack of enforcement of waterpipe tobacco control policies [6,12].…”
Section: Introductionmentioning
confidence: 99%
“…While cigarette smoking has been declining steadily in recent decades in Western countries (Salloum et al, 2017;Rezk-Hanna & Benowitz, 2018), many studies show that the use of hookah is on a trend of increase worldwide (Mo-hammed et al, 2016;Maziak et al, 2015;Salloum et al, 2017;Rezk-Hanna & Benowitz, 2018), both in developed countries (Krenik-Matejcek et al, 2017) and in developing countries (Saff ar Sofl aei et al, 2018). Hookah has also become the second most common tobacco use among young adults in the United States, after cigarettes which still rank fi rst in the use of tobacco (Rezk-Hanna & Benowitz, 2018). The growing popularity of hookah smoking can be attributed to several reasons, which generally include causes associated with the hookah itself, and reasons which are related to social and environmental motives.…”
Section: The Motives Of the Increased Usage Of Hookahmentioning
confidence: 99%
“…The hookah "enjoys" a less harmful image compared to cigarettes, partly because of the ambiguity regarding its components and what the smoker actually inhales to his/her lungs. One of these substances is nicotine, known as being addictive (Rezk-Hanna & Benowitz, 2018).…”
Section: The Unharmful Perception Of Smoking Hookahmentioning
confidence: 99%
“…[23][24][25][26][27][28] WPT smoking has been associated with increased risk for lung and oral cancers, coronary heart and pulmonary diseases. [29][30][31] The growing popularity of WPT smoking not only increases the number of smokers exposed to health risks [11][12][13][14][15][16][17][18][19][20] but also may lead to increases in environmental contamination due to the disposal of postconsumption WPT waste. Postsmoking WPT waste includes the smoked WPT residue (remnants of the heated WPT found in the WP head at the end of a smoking session), aluminium foil (that covers the WPT by wrapping it around the WP head to avoid burning the WPT), burnt charcoal (charcoal remnants after burning) and smoked WP water (water in the WP bowl through which WPT and charcoal smoke bubble during smoking); other WPT waste includes the packaging of the WPT.…”
Section: Introductionmentioning
confidence: 99%